El clima organizacional y su incidencia en el desempeño laboral de los servidores de la municipalidad distrital de Sanagorán – Huamachuco - Provincia de Sánchez Carrión año 2016 - Tamayo Baca, Hernán Duverli (2018)
The present investigation was carried out in the District Municipality of Sanagorán located in the Sánchez Carrión Province in La Libertad. Its general objective was to determine how the organizational climate affects the work performance of the servers of the District Municipality of Sanagorán - Sánchez Carrión Province, 2016; In this regard, the research problem was: What is the impact that exists between the organizational climate and the work performance of the Servants of the District Municipality of Sanagorán? Regarding the methodology, a non-experimental investigation, of causal transectional design was developed; the population was made up of 51 hired and appointed workers (between bosses and subordinates) of said municipality, being at the same time the sample; and in terms of data collection, the survey technique and the evaluation sheet technique applied by the heads were applied, whose instruments are the questionnaire and the evaluation sheet. According to the results obtained, the hypothesis has been demonstrated, which states that: "The organizational climate has a significant impact on the work performance of the servers of the District Municipality of Sanagorán to achieve institutional objectives." It is concluded that the organizational climate directly affects the work performance of the servers of the District Municipality of Sanagorán, since it has been determined based on scores that both variables qualify on a regular level; consequently, if the independent variable were at a good level, work performance would be better; Otherwise, if the weather is weak, the performance would be lower.